Stress hyperglycaemia in hospitalized patients with coronary artery disease and type 2 diabetes risk. (24th August 2013) - Colomo, Natalia; Linares, Francisca; Rubio‐Martín, Elehazara; Moreno, María J.; de, Manuel; García, Ana M.; González, Ana M.; Rojo‐Martínez, Gemma; Valdés, Sergio; Ruiz de Adana, María S.; Olveira, Gabriel; Soriguer, Federico
Abstract Background Aims: (i) To evaluate glucometabolic status of patients without known diabetes hospitalized due to coronary artery disease (CAD), (ii) to assess markers of systemic inflammation determined during admission and to evaluate their relationship with glucometabolic status and (iii) to analyse usefulness of HbA1c determined during admission in patients with CAD to detect abnormal glucose regulation (AGR). Materials & methods We studied 440 patients with CAD admitted to the cardiology ward. Patients were grouped in four groups during admission according to clinical data, fasting plasma glucose and HbA1c: diabetes, HbA1c > 5·9%, stress hyperglycaemia (SH) and normal. In 199 subjects without known diabetes, an oral glucose tolerance test (OGTT) was performed 3 months after discharge, and they were reclassified according to WHO 1998 criteria. Biochemical and inflammatory markers were measured. Results The OGTT showed that 27·4% of subjects without known diabetes at admission had diabetes, 11·2% had impaired fasting glucose + impaired glucose tolerance, 33·5% impaired glucose tolerance, 3·6% impaired fasting glucose, and 24·4% normal glucose metabolism. Odds ratio for having diabetes 3 months after discharge in HbA1c > 5·9% group was 5·91 (P < 0·0001) and in SH group was 1·82 (P = 0·38). The best HbA1c cut‐off point to predict AGR was 5·85%. HbA1c levels during admission were highly predictive of having AGR (AUC ROC 0·76 [95% CI 0·67–0·84]). Conclusion We reported a high prevalence of AGR in subjects with CAD. Stress hyperglycaemia in patients with CAD was not associated with an increased risk of diabetes 3 months later. HbA1c in patients hospitalized with CAD was a useful tool to detect AGR.